Determination of Nearest Emergency Service Office using Haversine Formula Based on Android Platform - Basyir, M.; Nasir, M.; Suryati, Suryati; Mellyssa, Widdha (Politeknik Elektronika Negeri Surabaya (PENS), 2017)
Emergency Reporting Application is an android-based application that serves to help the community in reporting the emergency condition. This application allows users to choose and contact the emergency services office, without the need to notice their position and phone number. Selection of emergency services office is also automatically selected by the system by taking into account the distance between the complainant and the emergency services office. The selected emergency services office is the nearest emergency service office from the complainant so that the delay in coming assistance can be minimized. Therefore, this proposed application requires a GPS feature to recording, reporting and SMS positioning for message delivery of reports. The distance between the position of the complainant and the position of the emergency service office, in the form of latitude and longitude data, is requested using the Haversine formula taking into account the degree of curvature of the earth. Emergency service offices include police and hospital offices spread over 25 different districts. Furthermore, the reporters position calculation results were compared with all selected emergency service offices and obtained 1 nearest emergency service office. Calculating the accuracy and delay value of the system will do system testing. Accuracy test results using the method of 100% Haversine and the average delay of the system is 4.5 seconds.